Gender as a Moderator of Eco-Digital Literacy and Sustainable Social Behavior in Paperless Learning Environments - Sima Fatmawati; Fathur Rohkman; Udi Utomo (Universitas Negeri Semarang, 2026)
This study aims to analyze the influence of eco-digital literacy on the sustainable social behavior of elementary school students in a paperless learning environment, as well as to test the role of gender moderation in this relationship. A quantitative approach with an explanatory survey design was used by involving 385 students from several elementary schools who had implemented paperless learning. Data was collected using a closed-ended questionnaire on a Likert scale and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) and Multi-Group Analysis (PLS-MGA) through SmartPLS 4. The results showed that eco-digital literacy had a positive and significant effect on sustainable social behavior (β = 0.614; t = 12.792; p < 0.001; R² = 0.577). PLS-MGA testing confirmed that gender moderated the relationship significantly (Δβ = 0.138; p = 0.048), with a stronger influence on the female group (β = 0.681) than on the male (β = 0.543). These findings provide important implications for the development of gender-responsive pedagogic-based curricula in the era of continuous digital learning.